Open Open Access sebagai Media Jaringan Kerjasama Perpustakaan Perguruan Tinggi - Yusniah Yusniah; Kartika Amelia Nasution; Sopa Rosa Lubis (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
In the current era of openness, the information and data presented are needed to provide the widest possible access to information to the public. The diversity of information needed and the limited information resources and changes in the behavior of information users make no single information institution able to meet the needs of all users. So that in meeting all the needs and optimal services to its users, cooperation is needed. Information institutions that need this collaboration are between libraries. The dissemination and exchange of information was carried out by various institutions. In this paper, we will discuss about open access which is a media for library collaboration. Currently, there are still a few libraries that have not implemented good open access, so there are still many libraries that do not dare to open information in full text. This research method is a qualitative method by collecting data to be used sourced from literature studies. The results of this study are to examine the implementation of open access which is used as a collaboration media, library.